Multivariate Analysis for Sustainable Water Management: Understanding and Managing Environmental Risks in the Ikopa Watershed, Madagascar - Ulrich, Fidelio Arnold; Bruno, Razanamparany; Robert, Rejo; Narindra, Ratiarimananjatovo; Nyiwa, Ngbolua Koto-Te-; Baholy, Robijaona Rahelivololoniaina (Budapest International Research in Exact Sciences (BirEx) Journal, 2024)
This paper delves into environmental challenges in Madagascar's Ikopa Watershed, focusing on the impact of climate disruptions and human activities on terrestrial and aquatic ecosystems. Employing a multidisciplinary approach, the research is examining the intricate interplay of geological, climatic, and human-induced factors, exploring their implications for sustainable water resource management. The study has employed representative sampling, surveying 386 households, and has combined it with field data collection and an evaluation of local perspectives on environmental risks. The results have identified four main forms of environmental degradation: water and wind erosion, biological, and water degradation. These phenomena have significant implications for water availability and quality, as well as local agricultural activities. Additionally, the research has classified households into two groups based on their exposure to climate variability, emphasizing the need for tailored adaptation strategies to address specific environmental challenges. The findings underscore the importance of local adaptation initiatives, such as sustainable land management and community awareness, to enhance resilience against environmental risks. Conclusively, the paper emphasizes the importance of ongoing and customized water resource management in the Ikopa Watershed, taking into account local perspectives, adaptation strategies, and future environmental challenges.